Faktor-Faktor Yang Mempengaruhi Ekuitas Merek Pada CV. Showroom Yulia Motor Sigambal - Zufrie Zufrie; Ali Sahputra (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
Researchers want to see how much the level of brand equity is influenced by price, brand awareness, and perceived quality. The method of data collection is through a questionnaire with a population of 98 people. Validity and reliability will be analyzed further from the results of the questionnaire as many as 98 respondents using quantitative analysis so as to produce feasibility for further testing. Data processing to determine the effect of variables using partial significance test (t test), simultaneous significance test (f test) and coefficient of determination (RÂ²). In the F test together, fcount is 18.960 > ttable is 2.47 and at (RÂ²) is 0.444 (44.4%), the results of the t-test are significant values where the comparison of tcount with ttable of the three X variables is greater than 1.986 or tcount is greater than ttable at a significant level of 95%.